Common Good and Self-Interest in Medieval and Early Modern Philosophy (Springer Nature, 2024)
This open access volume provides an in-depth analysis of philosophical discussions concerning the common good and its relation to self-interest in the history of Western philosophy. The thirteen chapters explore both renowned and lesser-known thinkers from the Middle Ages to the eighteenth century, covering also the relevant ancient background. By bridging the gap between the medieval and early modern periods, they provide fresh insights into how moral and political philosophers understood the concepts of the common good and self-interest, along with their ethical and political implications. The concept of the common good occupies a central role in philosophical reflections on the public and private dimensions of moral and social life in contemporary debates. By exploring the rich and diverse ways in which the relationship between the common good and self-interest has been understood, this volume has the potential to contribute to our ongoing efforts to critically discern the possibilities and limitations of these concepts in the present. Thus, the volume will be useful for scholars interested in the multi-layered role of the notion of the common good both in the history of philosophy and in contemporary moral and political philosophy.